Their God is too small Open Theism and the undermining of confidence in God - Ware, Bruce A. (Wheaton, IL Crossway, 2003)
Includes bibliographical referencesand indexes.
Keywords: God -- omniscience; Providence and government of God; Free will and determinism -- religious aspects -- Christianity